2021
DOI: 10.2217/nnm-2020-0441
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Against The Novel Coronavirus (Severe Acute Respiratory Syndrome Coronavirus 2): Diagnosis, Treatment, Therapy and Future Perspectives

Abstract: Coronavirus 2019 (COVID-19), as an emerging infectious disease, has caused significant mortality and morbidity along with socioeconomic impact. No effective treatment or vaccine has been approved yet for this pandemic disease. Cutting-edge tools, especially nanotechnology, should be strongly considered to tackle this virus. This review aims to propose several strategies to design and fabricate effective diagnostic and therapeutic agents against COVID-19 by the aid of nanotechnology. Polymeric, inorganic self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 149 publications
0
49
0
1
Order By: Relevance
“…The effect of immunosuppressant drugs on COVID-19 infection has been investigated which mainly incorporate corticosteroids, tocilizumab, and mycophenolic acid (MPA). In vitro studies have shown the growth inhibitory effects of MPA on SARS-CoV-2 [2]. Currently, the guidelines recommend the reduction and/or withdrawal of MPA in COVID-19 patients [2].…”
Section: Covid-19 and The Use Of Immunosuppressantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of immunosuppressant drugs on COVID-19 infection has been investigated which mainly incorporate corticosteroids, tocilizumab, and mycophenolic acid (MPA). In vitro studies have shown the growth inhibitory effects of MPA on SARS-CoV-2 [2]. Currently, the guidelines recommend the reduction and/or withdrawal of MPA in COVID-19 patients [2].…”
Section: Covid-19 and The Use Of Immunosuppressantsmentioning
confidence: 99%
“…In vitro studies have shown the growth inhibitory effects of MPA on SARS-CoV-2 [2]. Currently, the guidelines recommend the reduction and/or withdrawal of MPA in COVID-19 patients [2]. However, the results of recent studies might alter this approach.…”
Section: Covid-19 and The Use Of Immunosuppressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several nanotechnology-based strategies that may prove to be effective in anti-SARS-CoV-2 diagnostics and therapeutics. Although the polymeric, inorganic self-assembling materials, peptidebased nanoparticles have shown some promise against SARS-CoV-2 with respect to rapid diagnosis, the nanotechnology-based strategies for COVID-19 using polymeric-based nanostructured materials are thought to be a powerful tool that can be deployed against the SARS-CoV-2 owing to its safety profile, protective encapsulation of drugs, bio-compatibility and bio-degradability, and flexibility of modification to size, shape, and properties, which include drug administration (FDA) approved poly (lactic-co-glycolic acid) (PLGA) and polyethylene glycol (PEG) are FDA approved polymers [91,92]. Nanotechnology can also improve vaccine development, and the most promising outcome using nano-liposomes has been seen in the mRNA (S protein of SARS-CoV-2) vaccine which is encapsulated in nanoliposomes with specific physicochemical properties [93].…”
Section: Promise Of Nanotechnologies In Future Sars-cov-2 Treatments and Understanding Immunopathologymentioning
confidence: 99%
“…Breve panorámica del rol de la NyN en la lucha contra la COVID-19 La nanotecnología ha sido importante en la lucha contra la COVID-19 y se considera que jugará un papel cada vez más relevante tanto en la prevención y el diagnóstico, como en la mejora de sistemas de entrega de agentes antivirales y el desarrollo de estos últimos de manera que puedan ser específicamente diseñados contra el SARS-CoV-2, contexto en el que se han señalado como promisorios los materiales inorgánicos autoensamblados y las nanopartículas de base péptida (Rashidzadeh et al, 2021), así como la nanoformulación de drogas como el corticosteroide dexametasona (Lammers et al, 2020).…”
Section: Introductionunclassified